Intensi Kewirausahaan Dalam Kerangka Goal-Directed Behavior Model - Novi Chandra; Sucipto Asan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2023)
The Indonesian millennial generation, especially the student group, is the potential resources  for the development of  the Indonesian future economy. This research used the Goal-Directed Behavior Model to determine the relationship between attitudes, subjective norms, anticipated positive emotions, negative emotions, entrepreneurial desires, frequency of past behavior, per-ceived behavioral control on Indonesian students' entrepreneurial intentions. This research in-volved 365 respondents. This quantitative research uses an online survey using purposive sam-pling and non-probability methods. The PLS-SEM is used for data processing. The results showed a positive relationship between attitudes, subjective norms, anticipated negative emotions, perceived behavioral control, and entrepreneurial desire. This research also found a positive relationship between entrepreneurial desire, frequency of past behavior, and per-ceived behavioral control on entrepreneurial intentions. It is hoped that this research can pro-vide a theoretical contribution to the Goal-Directed Behavior model framework as well as con-tributions from entrepreneurship education institutions in Indonesia.